Pak1 as a novel therapeutic target for antihypertrophic treatment in the heart. - Liu, W; Zi, M; Naumann, R; Ulm, S; Jin, J; Taglieri, D; Prehar, S; Gui, J; Tsui, H; Xiao, R; Neyses, L; Solaro, R; et al. (2011)
BACKGROUND: Stress-induced hypertrophic remodeling is a critical pathogenetic process leading to heart failure. Although many signal transduction cascades are demonstrated as important regulators to facilitate the induction of cardiac hypertrophy, the signaling pathways for suppressing hypertrophic remodeling remain largely unexplored. In this study, we identified p21-activated kinase 1 (Pak1) as a novel signaling regulator that antagonizes cardiac hypertrophy. METHODS AND RESULTS: Hypertrophic stress applied to primary neonatal rat cardiomyocytes (NRCMs) or murine hearts caused the activation of Pak1. Analysis of NRCMs expressing constitutively active Pak1 or in which Pak1 was silenced disclosed that Pak1 played an antihypertrophic role. To investigate the in vivo role of Pak1 in the heart, we generated mice with a cardiomyocyte-specific deletion of Pak1 (Pak1(cko)). When subjected to 2 weeks of pressure overload, Pak1(cko) mice developed greater cardiac hypertrophy with attendant blunting of JNK activation compared with controls, and these knockout mice underwent the transition into heart failure when prolonged stress was applied. Chronic angiotensin II infusion also caused increased cardiac hypertrophy in Pak1(cko) mice. Moreover, we discovered that the Pak1 activator FTY720, a sphingosine-like analog, was able to prevent pressure overload-induced hypertrophy in wild-type mice without compromising their cardiac functions. Meanwhile, FTY720 failed to exert such an effect on Pak1(cko) mice, suggesting that the antihypertrophic effect of FTY720 likely acts through Pak1 activation. CONCLUSIONS: These results, for the first time, establish Pak1 as a novel antihypertrophic regulator and suggest that it may be a potential therapeutic target for the treatment of cardiac hypertrophy and heart failure.